2014
DOI: 10.1155/2014/132175
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury after Major Abdominal Surgery: A Retrospective Cohort Analysis

Abstract: Background. We analyzed the incidence, risk factors, and prognosis of acute kidney injury (AKI) in a cohort of patients undergoing major abdominal surgery. Methods. A total of 450 patients were retrospectively studied. AKI was defined by an increase in serum creatinine (SCr) ≥ 0.3 mg/dl or by an increase in SCr ≥ 50% and/or by a decrease in urine output to 0.5 ml/kg/hour for 6 hours, in the first 48 hours after surgery. Logistic regression method was used to determine predictors of AKI and in-hospital mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
50
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 45 publications
9
50
4
Order By: Relevance
“…[2][3][4] In our study, AKI after abdominal surgery had a negative impact on 30-day mortality, which was 18.2% in the AKI patients compared with 5.3% in the propensity score-matched control group. This is consistent with studies by both Teixeira et al 16 and Kheterpal et al, 15 who observed a rate of 20.8% and 15%, respectively. Furthermore, Kim et al 13 described a rather higher 30-day mortality of 31% of patients with AKI after nonvascular intra-abdominal surgery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…[2][3][4] In our study, AKI after abdominal surgery had a negative impact on 30-day mortality, which was 18.2% in the AKI patients compared with 5.3% in the propensity score-matched control group. This is consistent with studies by both Teixeira et al 16 and Kheterpal et al, 15 who observed a rate of 20.8% and 15%, respectively. Furthermore, Kim et al 13 described a rather higher 30-day mortality of 31% of patients with AKI after nonvascular intra-abdominal surgery.…”
Section: Discussionsupporting
confidence: 92%
“…However, direct comparison of these studies and the present one is difficult, as AKI was defined as an elevation of SCr >176.8 μmol/L above baseline or requirement for renal replacement therapy within 30 days after surgery in the previous studies. Interestingly, Teixeira et al 16 examined postoperative AKI after abdominal surgery using the KDIGO criteria and found an incidence of 22.4%, which is approximately 10-fold higher than the overall rate in our study. The difference between studies is most likely explained by limiting the inclusion to patients undergoing major surgery in a tertiary care setting and who were predicted to stay in hospital for at least 48 hours.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Sepsis-associated AKI (SA-AKI) is even considered as a distinct subtype of AKI due to its unique pathophysiology (Alobaidi et al 2015). AKI is also a serious complication in surgical patients with major abdominal surgery and sepsis as some of the most important risk factors (Kheterpal et al 2009;Teixeira et al 2014).…”
Section: Introductionmentioning
confidence: 99%